An Analysis of Indonesia's Trade Strategy Amid the Dynamics of the Indo-Pacific Economic Architecture: A Comparative Study of the Regional Comprehensive Economic Partnership (RCEP) and the Indo-Pacific Economic Framework for Prosperity (IPEF) - Mohamad Azis Ramadhan; Dwi Fauziansyah Moenardy (Eduvest - Journal of Universal Studies, 2026)
The background of this research is grounded in the growing rivalry between the United States and China, which has produced two economic cooperation frameworks with different characteristics. RCEP provides tangible benefits through market access, tariff reduction, and regional economic integration, while IPEF emphasizes modern economic standards, supply chain resilience, digital economy, clean economy, and fair governance. This research examines Indonesia’s trade strategy amid the changing economic architecture of the Indo-Pacific through comparative research of the Regional Comprehensive Economic Partnership (RCEP) and the Indo-Pacific Economic Framework for Prosperity (IPEF). This study aims to analyze how Indonesia, as a middle power, applies a hedging strategy to optimize its national trade interests between these two frameworks. This research employed a qualitative approach using comparative study and documentation analysis of official documents, trade data, international institutional reports, and relevant academic literature. The findings indicate that Indonesia implements a hedging strategy through trade partner diversification, optimization of RCEP’s economic benefits, fulfillment of IPEF commitments, and preservation of foreign policy autonomy. Indonesia’s simultaneous participation in RCEP and IPEF is not contradictory; rather, it is complementary in strengthening Indonesia’s position amid Indo-Pacific economic competition. The research implies the need for a strategic trade policy roadmap that balances economic interests, national autonomy, and Indonesia’s commitment to regional stability.